2019
DOI: 10.1055/a-0961-1458
|View full text |Cite
|
Sign up to set email alerts
|

Fate Tracing of Isl1+Cells in Adult Mouse Hearts under Physiological and Exercise Conditions

Abstract: Myocardial damage due to dysfunctional myocardium has been increasing, and the prognosis of pharmacological and device-based therapies remain poor. Isl1-expressing cells were thought to be progenitor cells for cardiomyocyte proliferation after specific stimuli. However, the true origin of the proliferating myocardiac cells and the role of Isl1 in adult mammals remain unresolved. In this study, Isl1-CreERT2 knock-in mouse model was constructed using CRISPR/Cas9 technology. Using tamoxifen-inducible Isl1-CreERT/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…ISL1, a transcription factor, fulfills diverse roles across multiple organs during embryonic development, and, within cardiac development, it serves as a marker for second heart field progenitors [65]. Its expression is detectable as early as E7 in mouse heart development, and its pattern shifts as development progresses, with the expression being observed in the SAN from postnatal stages through to adulthood [66]. In zebrafish, Isl1 is a marker for pacemaker cells located at the junction of the sinus venosus and atrium, where it is necessary for normal pacemaker function and development [67].…”
Section: Islet-1 (Isl1)mentioning
confidence: 99%
“…ISL1, a transcription factor, fulfills diverse roles across multiple organs during embryonic development, and, within cardiac development, it serves as a marker for second heart field progenitors [65]. Its expression is detectable as early as E7 in mouse heart development, and its pattern shifts as development progresses, with the expression being observed in the SAN from postnatal stages through to adulthood [66]. In zebrafish, Isl1 is a marker for pacemaker cells located at the junction of the sinus venosus and atrium, where it is necessary for normal pacemaker function and development [67].…”
Section: Islet-1 (Isl1)mentioning
confidence: 99%
“…By E14.5, Isl1 expression only persists in a subset of cells in the heart, including subdomains within the OFT, RV, venous valves, aorta, pulmonary artery, atrial septum, and in regions of sinoatrial node (SAN), atrioventricular node (AVN), and in clusters of cells of cardiac ganglia ( Sun et al, 2007b ). From postnatal stage to adulthood, Isl1 expression is still observed in several cell types of the heart, which are localized in the SAN, very few if any in the AVN, at the base of the aorta and pulmonary artery and in cardiac ganglia ( Moretti et al, 2006 ; Sun et al, 2007b ; Weinberger et al, 2012 ; Zhou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a number of studies have produced clear evidence that, in accordance with its expression profile, Isl1 marks the SHF progenitors during cardiogenesis ( Cai et al, 2003 ; Moretti et al, 2006 ; Bu et al, 2009 ; Gao et al, 2019 ), even though Isl1 was found to be transiently detected in a small number of cells in the FHF ( Ma et al, 2008 ). Interestingly, there have been reports of small numbers of Isl1 + cells being detected in the hearts of adult mice ( Genead et al, 2010a ; Khattar et al, 2011 ; Weinberger et al, 2012 ; Zhou et al, 2019 ), but there is growing evidence to suggest that these cells may not be functioning as CPCs ( Weinberger et al, 2012 ; Zhou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%